KAJIAN KOMPREHENSIF TENTANG KONSEP MAKKIYAH DAN MADANIYAH DALAM ULUMUL QUR’AN - Afifatul Aspia; Najwa Khoiriyah; Nur Elma; Nur Fathia Sari; Akhmad Dasuki (PT. Hasba Edukasi Mandiri, 2025)
This article discusses the concepts of Makkiy and Madaniy within the discipline of Ulumul Qur’an, focusing on differences in timing, location, characteristics, and the methods used to classify the Qur’anic verses revealed during the two phases of the Prophet Muhammad’s mission. The study employs a descriptive approach supported by classical and contemporary literature that explains the meanings, features, and significance of understanding Makkiy and Madaniy classifications. The findings reveal that this knowledge is not only related to the historical revelation of the Qur’an but also crucial for understanding the socio-historical context, da'wah strategies, and the gradual development of Islamic law. A comprehensive understanding of these categories helps prevent misinterpretation and strengthens insight into the dynamics of the Prophet’s mission. Thus, the concepts of Makkiy and Madaniy hold an essential role in the study of Qur’anic sciences and serve as a foundation for deeper analysis of the Qur’anic message.